A Bayes Estimator of Parameters of Nonlinear Dynamic Systems. (19th July 2009) - Boguslavsky, I. A.
Abstract : A new multipolynomial approximations algorithm (the MPA algorithm) is proposed for estimating the state vector θ of virtually any dynamical (evolutionary) system. The input of the algorithm consists of discrete-time observations Y . An adjustment of the algorithm is required to the generation of arrays of random sequences of state vectors and observations scalars corresponding to a given sequence of time instants. The distributions of the random factors (vectors of the initial states and random perturbations of the system, scalars of random observational errors) can be arbitrary but have to be prescribed beforehand. The output of the algorithm is a vector polynomial series with respect to products of nonnegative integer powers of the results of real observations or some functions of these results. The sum of the powers does not exceed some given integer d . The series is a vector polynomial approximation of the vector E ( θ ∣ Y ), which is the conditional expectation of the vector under evaluation (or given functions of the components of that vector). The vector coefficients of the polynomial series are constructed in such a way that the approximation errors uniformly tend to zero as the integer d increases. These coefficients are found by the Monte-Carlo method and a process of recurrent calculations that do not require matrix inversion.